The determination of the effect of some 1,3,4 thiadiazole derivatives on biochemical content (Fatty Acids, Sterols, Lipophilic Vitamins) in rat liver - Parlak, Akif E.; Karagozoglu, Yusuf; Alayunt, Naci O.; Turkoglu, Semra; Karatepe, Mustafa; Koparir, Metin (C M B Assoc, 2018)
Thiadiazole derivatives and its metal compounds have antibacterial, antifungal, antitumoral, antiproliferative and antioxidant properties. In the study, the effects caused by thiadiazole ligand and its metal complexes upon the fatty acids and lipophilic vitamins in livers of rats were examined. The fatty acids in liver were specified by GC while the lipophilic vitamins were specified by HPLC. It was observed that the amounts of oleic acids (18: 1, n-9) and monounsaturated fatty acids (MUFA) notably increased in the Mn complex group while the amounts of arachidonic acid (20: 4, n-6) notably increased in the ligand group, compared to control group. The amounts of vitamin K-2, vitamin D-3 and a-tocopherol considerably increased in all groups compared to control group. It was noted that the amounts of a-tocopherol were elevated in both the Mn and Cr complex groups compared to control group. However, this elevation was matching with the amount in the same groups. Nevertheless, the amount of retinol was determined to be lower in the Mn complex group compared to other groups. Accordingly, it can be considered that thanks to the utilization of toxic metals such as manganese, cadmium and chrome, unsaturated fatty acids influenced the activities of the enzymes in liver tissue, which are in charge of fatty acid chain elongation.
Keywords: Hydroxyurea Derivative 1, 3, 4-thiadiazole; Fatty acid; Lipophilic vitamin; Liver; Rat